An adaptive channel estimation scheme based on redundancy minimization for filtered OFDM networks - Ahmad Hasan; Sam Motakabber; Mohamed Hadi Habaebi; Farhat Anwar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Filtered orthogonal frequency division multiplexing (F-OFDM), a technology which is being considered as a promising platform for beyond 4G era is expected to help deliver the new features at millimeter wave in the new 5th generation of cellular communication. Some of its key features notably better spectral utilization, enhanced throughput and immunity to interference can be enabling for the new cellular standards. These features of filtered OFDM comes with strict requirements of filter design, guard tone managements, and efficient channel state information harness. This paper is intended to propose an intuitive channel estimation scheme which will allow efficient acquisition of channel state information (CSI) through exploiting the redundant steps of the conventional pilot training-based algorithms and by also using an adaptive weight to expedite the minimization of the error between the estimated values and the actual values. Various simulations will follow to demonstrate the superiority of the scheme over traditional pilot-based algorithms and thus prove its utility in the current 5G cellular era.